New Challenges faced by the Faculty of Civil and Mechanical Engineering of the Technical University of Ambato (U.T.A) - Medina Pazmiño, Wilson (2022)
Dear Editor:   Receive my respects, a cordial greeting and my gratitude for the honor granted to recount my experiences teaching at what is now the Faculty of Civil and Mechanical Engineering of the Technical University of Ambato.   Over time, Civil Engineering and Mechanical Engineering have been technically and scientifically strengthening within a framework of responsibility and those principles of honesty, integrity and professional truthfulness, however the evolution of technology and the multiple technical problems in which civil and mechanical engineers are involved define a more determined and firm commitment that allows professional engineers to claim and give at the same time the share of citizen consensus that we cannot deny; not only when the country needs of our greatest technical contribution; not only when the solution of the problems require greater preparation; is when we must intensify efforts to update and strengthen our knowledge, but because it is our obligation to make this task permanent as the modern society demands the effective and real participation of all the actors who have the privilege of having a share of knowledge in the consensus of our society, since science is a heritage of humanity and not of a certain group or individual. The initial stages of the Faculty of Civil and Mechanical Engineering of the UTA, summing up briefly and succinctly, have their origin in the Higher Institute of Accounting and Auditing, that after an arduous effort and management is transformed into what is today the Technical University of Ambato, creating at that time different faculties, among them the Engineering Faculty with three schools: School of Food Engineering, School of Agronomic Engineering and School of Civil Engineering; which later become three Faculties: Faculty of Food Sciences and Engineering, Faculty of Agronomy and Faculty of Civil Engineering which later incorporated  Mechanical Engineering converting itself into the Faculty of Civil and Mechanical Engineering. The role played by the Faculty of Civil and Mechanical Engineering has been fundamental in the Province and the Country, given that it has always set the pace with scientific progress in the area of ??knowledge, especially in Earthquake Resistance. Considering that Ecuador and specifically the city of Ambato present high seismic risk; it is important to highlight three components that combined define the risk: Seismic Hazard, Vulnerability and Exposed Elements, which lead to the probability of human, economic or social losses. The seismic hazard cannot be avoided, as it is part of a natural phenomenon; on the other hand, the vulnerability depends on the chosen structural system, in other words, to lower the risk we must lower the vulnerability; by analyzing, calculating and optimizing projects and structures in accordance with the latest codes and state-of-the-art technology. Japan can be set as an example of a country with high seismic hazard, but low seismic risk due to the low vulnerability of its buildings, since its constructions are designed and executed with the highest technology according to the most demanding codes. Ecuador, on the other hand, is a country with high seismic hazards and high seismic risk, since its constructions are highly vulnerable; with a few honorable exceptions. Therefore, the role of the young engineers who graduated from our beloved faculty would be framed in investigating, evaluating and providing solutions to many infrastructure works throughout the country that require to be reinforced under new concepts of performance levels such as heritage buildings, private buildings, bridges, etc. and thus, reduce their vulnerability and protect human lives, which in the end is the main purpose of earthquake-resistant design.